The reality of teaching the digital skills course in the primary school: challenges and solutions in light of digital transformation - Alhabish, Mohamed Saeed; Alqarni, Ahmed Mohsen; Alqarni, Ali Mohammed; Alghamdi, Abdulrahman Mohammed; Albarbi, Asim Homod; Almuntashiri, Abdulkarim Saleh (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to reveal the reality of teaching the digital skills course in the primary stage from the point of view of teachers, the challenges they face, and the proposed solutions in light of digital transformation in government public schools in Jeddah Governorate. To achieve these objectives, the study used the descriptive (survey) approach and its questionnaire. It was distributed to a random sample of (99) teachers, which constituted (26.2%) of the study population, which amounted to (378) teachers. This indicated their agreement on the existence of challenges related to the computer lab, with an arithmetic mean of (3.62), and their neutrality regarding administrative challenges, where the arithmetic mean was (3.17). The study recommended many recommendations and research proposals, including providing a hard copy of the digital skills course for students, and providing alternative applications for the programs taught in the course that work on smart phones.
Keywords: the reality of teaching digital skills; the challenges of teaching digital skills; digital transformation